2009
DOI: 10.3144/expresspolymlett.2009.73
|View full text |Cite
|
Sign up to set email alerts
|

How carbon nanotubes affect the cure kinetics and glass transition temperature of their epoxy composites? – A review

Abstract: Abstract. Motivated by the widespread and contradictory results regarding the glass transition temperature of carbon nanotube (CNT)/epoxy composites, we reviewed and analyzed the literature results dealing with the effect of unmodified multiwall carbon nanotubes (MWNT) on the cure behaviour of an epoxy resin (as a possible source of this discrepancy). The aim of this work was to clarify the effective role of unmodified multiwall carbon nanotubes on the cure kinetics and glass transition temperature (Tg) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 26 publications
5
94
0
1
Order By: Relevance
“…One possible explanation of these results was that the cross-linking degree of both oxazine rings and nitrile groups had been improved by the assistance of BPA, affording a reaction-induced microphase separation. As was well known, the T g of polymers depends on the rigidity of the molecular chains and the cross-linking degree [35][36][37][38][39][40]. It can be seen in Table 5 that the T g 1 of the samples were up to 240°C, which were superior to the traditional epoxy, phenolics and polybenzoxazines resin [36][37][38][39][40].…”
Section: Dynamic Thermomechanical Analysis Of the Ba-ph/bpa/gf Composmentioning
confidence: 63%
“…One possible explanation of these results was that the cross-linking degree of both oxazine rings and nitrile groups had been improved by the assistance of BPA, affording a reaction-induced microphase separation. As was well known, the T g of polymers depends on the rigidity of the molecular chains and the cross-linking degree [35][36][37][38][39][40]. It can be seen in Table 5 that the T g 1 of the samples were up to 240°C, which were superior to the traditional epoxy, phenolics and polybenzoxazines resin [36][37][38][39][40].…”
Section: Dynamic Thermomechanical Analysis Of the Ba-ph/bpa/gf Composmentioning
confidence: 63%
“…Numerous studies on cure kinetics of epoxy in presence of carbon-based nanofillers have been investigated [16][17][18][19][20][21][22][23][24][25]. Recently, Allaoui and El Bounia [16] had reviewed the influence of CNTs on the cure kinetics of epoxy resin. Our previous studies showed that the addition of CNTs could accelerate the cure reaction of epoxy resin, while CNFs had only a negligible effect on the cure kinetics of the epoxy [17,18].…”
mentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) may be considered as one of the most interesting techniques for kinetic analysis of cure reactions of thermosetting systems [13][14][15]. Numerous studies on cure kinetics of epoxy in presence of carbon-based nanofillers have been investigated [16][17][18][19][20][21][22][23][24][25]. Recently, Allaoui and El Bounia [16] had reviewed the influence of CNTs on the cure kinetics of epoxy resin.…”
mentioning
confidence: 99%
“…Additionally, the variation of T g as a function of filler content in epoxy nanocomposites shows an initial decrease up to a certain content value followed by an increase at higher filler loading [8,9]. Therefore, the actual effect of the filler on the T g necessitates further clarification, as it is also reviewed for MWCNT composites in [10]. In general, the amount, the dispersion and the surface conditions of the nanoparticles were found to play an important role in the variation of T g and the mechanical properties of the nanocomposites [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%